Development and Performance Evaluation of a Poultry Bird Defeathering Machine - Olufemi Adeyemi Adetola (ABUAD Journal of Engineering Research and Development)
The poultry processing industry is under high demand due to the increasing demand for chicken meat worldwide, especially in Sub-Saharan Africa, where manual defeathering is the norm. The primary objectives of this study were the design, construction, and performance evaluation of a chicken defeathering machine using locally accessible materials. Standard equations and formulae were used in the design of the machine's main parts, which include the electric motor, sheave, belt, pulley, bearing, feather plate, rubber fingers, cylindrical drum, and rubber pluckers. Fifteen cockerel chickens of different weights were evaluated at three different speeds of 450, 500, and 550 rpm in order to assess the performance of the chicken feather plucking machine. The data obtained was analyzed using Excel 13. The highest defeathering efficiency of 84.49% was recorded at a machine speed of 450 rpm, followed by a defeathering efficiency of 81.70% at a machine speed of 500 rpm, while the lowest defeathering efficiency of 80.98% was recorded at a machine speed of 550 rpm, respectively. The highest plucking time of 22.80 s was recorded at a machine speed of 450 rpm, followed by a plucking time of 20.40 s at a machine speed of 500 rpm, while the lowest plucking time of 19.80 s was recorded at a machine speed of 550 rpm, respectively. It will take an average of 21.00 seconds to defeat a medium cockerel used for the testing of the defeathering, which implies that the developed defeathering machine can defeat 171 chickens per hour. The machine is powered by a 5.5-hp, three-phase electric motor and has a production cost of $250, with the construction materials being locally available at affordable costs. The machine is recommended to both small and medium-scale farmers and food processors due to its simplicity, cost-effectiveness, and improvement over the previous ones in terms of efficiency and capacity.